2000
DOI: 10.1080/000486700265
|View full text |Cite
|
Sign up to set email alerts
|

Down will Come Baby, Cradle and All: Diagnostic and Therapeutic Implications of Chronic Trauma on Child Development

Abstract: Exposure to intrafamilial violence and other chronic trauma results in pervasive psychological and biological deficits. Treatment needs to address issues of safety, stabilise impulsive aggression against self and others, promote mastery experiences, compensate for specific developmental deficits, and judiciously process both the traumatic memories and trauma-related expectations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(68 citation statements)
references
References 82 publications
1
63
0
Order By: Relevance
“…Adverse childhood experiences create toxic stress, leading to an over-production of hormones associated with survival responses (fight or flight), and producing neurobiological changes in the brain that can impede cognitive processing and selfregulation capacities (Alink, Cicchetti, Kim, & Rogosch, 2012;Creeden, 2009;Finkelhor & Kendall-Tackett, 1997;SAMHSA, 2014a;Streeck-Fischer & van der Kolk, 2000;van der Kolk, 2006). Research has indicated that the multiplicity, frequency, and chronicity of early adversity creates what has become known as complex post-traumatic stress, manifesting in a constellation of maladaptive coping strategies, mental health symptoms, and behavioral problems (Cloitre et al, 2009;Herman, 1992;van der Kolk, 2014).…”
Section: Adverse Childhood Experiencesmentioning
confidence: 99%
“…Adverse childhood experiences create toxic stress, leading to an over-production of hormones associated with survival responses (fight or flight), and producing neurobiological changes in the brain that can impede cognitive processing and selfregulation capacities (Alink, Cicchetti, Kim, & Rogosch, 2012;Creeden, 2009;Finkelhor & Kendall-Tackett, 1997;SAMHSA, 2014a;Streeck-Fischer & van der Kolk, 2000;van der Kolk, 2006). Research has indicated that the multiplicity, frequency, and chronicity of early adversity creates what has become known as complex post-traumatic stress, manifesting in a constellation of maladaptive coping strategies, mental health symptoms, and behavioral problems (Cloitre et al, 2009;Herman, 1992;van der Kolk, 2014).…”
Section: Adverse Childhood Experiencesmentioning
confidence: 99%
“…A traumatic event may be defined as an event that is overwhelming to the child's senses or self-regulatory abilities, threatens the child's well-being or that of their caregiver, indicates the world is uncontrollable and unpredictable, and/or involves stressors that exceed the child (or caregiver's) normal resources (Cordón, et al, 2004;Van Horn & Lieberman, 2008). Chronicity of trauma (Streeck-Fischer & Van der Kolk, 2000), the child's pretrauma adjustment (Feldman & Vengrober, 2011), and the caregiver's reaction to the trauma (DeVoe, Klein, Bannon, & Miranda-Julian, 2011) have all been linked to the severity of children's post-trauma functioning.…”
Section: Early Childhood Traumamentioning
confidence: 99%
“…The process of attachment is arguably most important in the earliest years, as it creates a biological framework for managing future stress and arousal (Streeck-Fischer & Van der Kolk, 2000), thus shaping how a child interprets and reacts to future experiences. As infants are not able to decipher between distinct, different arousal states or verbalize their needs, they are dependent on caregivers to modulate their arousal and to care for their basic needs ( Van der Kolk, 2006).…”
Section: Development Attachmentmentioning
confidence: 99%
See 2 more Smart Citations